Fibrinogen Mahdia: A congenitally abnormal fibrinogen characterized by defective fibrin polymerization. Issue 4 (8th June 2017) - Amri, Y.; Jouini, H.; Becheur, M.; Dabboubi, R.; Mahjoub, B.; Messaoud, T.; Sfar, M. T.; Casini, A.; de Moerloose, P.; Toumi, N. E. H.
Abstract : Introduction: Congenital dysfibrinogenemia is a rare qualitative fibrinogen deficiency. Molecular defects that result in dysfibrinogenemia are usually caused by mutations which affect fibrinopeptide release, fibrin polymerization, fibrin cross‐linking or fibrinolysis. Aim: Here, we investigated the genetic basis of hypodysfibrinogenemia in two Tunisian siblings with major bleeding. Methods: Coagulation‐related tests were performed on the patients and their family members. Functional analysis was performed in plasma fibrinogen to characterize fibrin polymerization. The sequences of fibrinogen genes were amplified and analysed by sequencing. Results: Coagulation studies revealed a reduced functional and a borderline low antigenic fibrinogen plasma levels with prolonged thrombin and activated partial thromboplastin times. The fibrinogen is also characterized by a markedly impaired polymerization and could incorporate into fibrin fibres to a smaller extent (22%). Mutational screening disclosed a heterozygous single nucleotide deletion (G) at c.1025, resulting in a frameshift mutation (AαGly323GlufsX79) that is predicted to delete a part of the αC‐domain containing some of the FXIII cross‐linking sites. Both the normal and the aberrant Aα‐chain (approximately 43 kDa) were detected by electrophoretic analysis in the patients. Conclusion: The new dysfunctional fibrinogen, Mahdia variant, describes its impact on fibrin assembly after the loss of the αC domains which are involved in the lateral aggregation of protofibrils. The study confirms that the truncated Aα‐chain could be incorporated into mature fibrinogen molecules.